Enhancing Argumentative Writing Proficiency Students in EFL Classroom: Leveraging Contextual Learning Models and Critical Thinking Competence - Muhammad Ilham Ali; Herminus Efrando Pabur (Institute of Educational, Research, and Community Service, 2023)
The study explained the influence of the contextual learning model and critical thinking competence in enhancing argumentative writing proficiency. The sample is 50 students taken by using a multistage sampling technique. The study results indicated that the contextual learning model group has more significant influence than the non-contextual learning model group. There was an interaction between the learning model and critical thinking competence. There was a significant argumentative writing skill difference between the contextual learning model group and the non-contextual learning model group with high critical thinking competence. The argumentative writing skill and contextual learning model were the same as the argumentative writing skill and non-contextual learning model group of low critical thinking ability. This means that critical thinking competence and contextual learning models have a significant influence on argumentative writing proficiency.